2013
DOI: 10.1177/0272989x13480852
|View full text |Cite
|
Sign up to set email alerts
|

Comparing EQ-5D Valuation Studies

Abstract: Background. There has been a growing interest around the world in developing country-specific scoring algorithms for the EQ-5D. This study systematically reviews all existing EQ-5D valuation studies to highlight their strengths and limitations, explores heterogeneity in observed utilities using meta-regression, and proposes a methodological checklist for reporting EQ-5D valuation studies. Methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(33 citation statements)
references
References 34 publications
0
32
0
1
Order By: Relevance
“…The EQ-5D-3L, regarded as the primary valuation study derived utility scores, are prevalently applied preference-based measures. 9,15,33 In this study, CER and ICERs were the outcomes of economic benefits, which could be comprehended that ICERs indicate how much extra health benefits via ELA can bring compared with via STA, and how much additional expense it will cost.…”
Section: Discussionmentioning
confidence: 98%
“…The EQ-5D-3L, regarded as the primary valuation study derived utility scores, are prevalently applied preference-based measures. 9,15,33 In this study, CER and ICERs were the outcomes of economic benefits, which could be comprehended that ICERs indicate how much extra health benefits via ELA can bring compared with via STA, and how much additional expense it will cost.…”
Section: Discussionmentioning
confidence: 98%
“…The Iranian valuation study 12 was conducted in the capital city of Iran with specific health–cultural–socio-economic status which might not be representative of the Iranian general population (eg, highly educated participants of whom 42% had academic education and solely from urban areas). A recent systematic review 22 showed that education, urbanisation, and healthcare expenditure are associated with utilities attributed to the EQ-5D-3L valuations indicating that the generalizability of the Iranian value set might be limited. In addition, it is not clear on what grounds the final model for the Iranian value set 12 has been selected.…”
Section: Discussionmentioning
confidence: 99%
“…With only few exceptions (e.g. Shaw et al, 2010), health state valuation studies have used the arithmetic mean to aggregate individual preferences into a societal preference (Xie et al, 2014;MVH, 1995). If the tariff would reflect (health-related)…”
Section: Problem Statementmentioning
confidence: 99%
“…If all individuals had similar preferences, however, the choice of the aggregation method would be trivial. Yet, empirical studies show that health state preferences differ considerably (Xie et al, 2014; also see figure 2), and the societal preference is thus intimately dependent on the method of aggregation -if the method is changed, the outcome might differ. This raises the question: how should preferences be aggregated?…”
Section: Problem Statementmentioning
confidence: 99%